Psychological and educational learning strategies and models during the COVID-19 pandemic: A comparative bibliometric analysis - Alshahrani, Abdullah Falah M. (Frontiers in Psychology, 2022)
This paper aims to analyse the literature review of psychological, Educational Learning Strategies, and Models during the COVID-19 Pandemic; The data of 359 publications relating to this subject published on the Web of Science, Scopus and ScienceDirect between 2020 and 2021 were examined by using bibliometric analysis adapted with VOSviewer software.The finding discusses the following approaches (keywords, authors, references (research papers), research work, countries, and research institutions). Finally, the review concluded that Bibliometric analysis is fundamental in detailing the theoretical literature and developing an integrated theoretical framework for psychological and Educational Learning Strategies. Therefore, the psychological impact on students and potential stress needs to be closely monitored and evaluated, to plan effective policies while adopting these pedagogical approaches.